The Influence of Digital Interactive Media and Immersive Experiences on Visitors' Educational Experiences at the Jakarta Maritime Museum - Dicky Juansyah Herwanto; Ika Suryono Djunaid (Darul Yasin Al Sys, 2026)
Advances in digital technology have transformed museums from institutions primarily devoted to collection preservation into increasingly interactive and immersive learning environments. Nevertheless, empirical evidence concerning the effects of digital interactive media and immersive experiences on visitors’ educational experiences remains limited, particularly in the context of the Jakarta Maritime Museum. This study aims to analyze the partial and simultaneous effects of digital interactive media and immersive experiences on visitors’ educational experiences at the Jakarta Maritime Museum. A quantitative survey design was employed, involving 100 museum visitors selected using the Slovin formula. Data were collected through questionnaires and analyzed using SPSS version 25 through validity and reliability testing, classical assumption testing, multiple linear regression, t-tests, an F-test, and coefficient of determination analysis. The findings indicate that digital interactive media have a positive and significant effect on visitors’ educational experiences (t = 8.061, p < .001), while immersive experiences also exert a positive and significant effect (t = 7.903, p < .001). Simultaneously, both variables significantly predict visitors’ educational experiences (F = 67.933, p < .001), with a coefficient of determination of R² = .583, indicating that they explain 58.3% of the variance in visitors’ educational experiences. The study concludes that optimizing digital interactive media and immersive experiences can strengthen the educational value of museum visits. These findings contribute to research on technology-enhanced museum learning and imply that the Jakarta Maritime Museum should develop more interactive, engaging, and immersive collection-presentation strategies to reinforce its educational function.